A study on the influence of environmental responsible leadership on employee pro-environmental behavior - Zhao, Cundong; Liang, Liping (Frontiers in Environmental Science, 2023)
As the public's call for corporate green development grows, more and more companies are joining the green development team. Environmental responsible leadership, as a leadership style focused on the construction of enterprises, has attracted widespread attention from the corporate and academic communities. Meanwhile, the pro-environmental behavior of employees is the key link in the implementation of green policies in enterprises. To clarify the mechanism of environmental responsible leadership on employee pro-environmental behavior, a moderated mediation model was constructed. This model examined the mediating role of employment relationship atmosphere between environmental responsible leadership and employee pro-environmental behavior, and examined the moderating role of social distance on the relationship between environmental responsible leadership and employment relationship atmosphere. The employment relationship atmosphere focuses on the level of trust, respect, and cooperation between managers and employees. Within a good employment relationship atmosphere, employees find that environmental responsible leaders treat them positively, and according to social exchange theory, in order to give back to the leaders, employees will take the initiative to perform the behaviors expected by the leaders, such as employee pro-environmental behaviors. We conducted a study on employees of five enterprises in Shanxi Province, and analyzed the questionnaire data using SPSS and AMOS. The results showed that environmental responsible leadership has a significant positive effect on employee pro-environmental behavior; employment relationship atmosphere plays a mediating role between environmental responsible leadership and employee pro-environmental behavior; social distance plays a moderating role in the relationship between environmental responsible leadership and employment relationship atmosphere, that is, the closer the social distance, the stronger the impact of environmental responsible leadership on employment relationship atmosphere.